Joint proposals to the UK Government for revisions to the Copyright Designs and Patents Act 1988 - Stratton, Barbara (2006)
Presents proposals for essential revisions to the Act in order to meet the realities of the provision of library, archive and cultural institutional services in the public and not-for-profit sectors of the UK economy and the use by readers of their resources at the start of the 21st century. Suggests amendments that reflect the need for the Act's revision of the WIPO Copyright Treaty 1996 so as to ensure that the normal exceptions and limitations to copyright in the UK apply without question to the use in the digital environment.